2019
DOI: 10.3390/sports7050124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coexistent Plantaris Tendon Pathology in Patients with Mid-Portion Achilles Pathology: A Retrospective MRI Study

Abstract: Co-existence of Plantaris tendinopathy (PT) in patients with mid-Achilles tendinopathy (Mid-AT) is of clinical significance. This study aims to describe the MRI-based pathological characteristics of co-existing PT and Mid-AT. One-hundred MRI studies of patients diagnosed with Mid-AT were retrospectively analysed by an experienced musculoskeletal radiologist. Presence or absence of a Plantaris tendon, co-existing PT with Mid-AT, insertional characteristics of Plantaris tendon, and maximum anteroposterior thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Recent research has demonstrated that plantaris tendon involvement can be found in patients with chronic midportion and insertional Achilles tendon tendinopathy, especially when there is medial Achilles tendon pain [ 19 , 34 , 35 , 36 ]. Cadaveric studies have demonstrated that there is an individual variability of the course of the plantaris tendon in relation to the Achilles tendon, with up to nine different courses demonstrated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that plantaris tendon involvement can be found in patients with chronic midportion and insertional Achilles tendon tendinopathy, especially when there is medial Achilles tendon pain [ 19 , 34 , 35 , 36 ]. Cadaveric studies have demonstrated that there is an individual variability of the course of the plantaris tendon in relation to the Achilles tendon, with up to nine different courses demonstrated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this dissonance, coexisting tendinopathies were found in 10% of the examined cases. 31 When conservative treatments for mid-substance Achilles tendinopathy with associated plantaris pathology fail, plantaris excision with or without Achilles tenosynovectomy has demonstrated good surgical outcomes for both recreational and high-level athletes. 32 - 34 …”
Section: Discussionmentioning
confidence: 99%
“…Plantaris tendon-related pain is a relatively new diagnosis, mainly found in a subgroup of elite or recreationally active individuals [ 5 , 7 , 17 ]. There is typically pain on the medial side of a thickened Achilles midportion; sometimes described as sudden and sharp pain, but more often described as dull pain during loading.…”
Section: Discussionmentioning
confidence: 99%